Prevalence and socio-structural determinants of tobacco exposure in young women: Data from the Healthy Trajectories Initiative (HeLTI) study in urban Soweto, South Africa. (1st March 2022) - Soepnel, Larske M.; Kolkenbeck-Ruh, Andrea; Crouch, Simone H.; Draper, Catherine E.; Ware, Lisa J.; Lye, Stephen J.; Norris, Shane A.
Abstract: Background: : Tobacco use is a major public health risk worldwide, which has increased on the African continent over the past 40 years. Socio-economic factors impact tobacco use and exposure, but little is known about the scope of this problem in young women living in an urban, historically disadvantaged township in contemporary South Africa. This study aimed to identify the prevalence of tobacco use in a cohort of young South African women using serum cotinine, and to assess the association between a number of socio-economic and social factors and tobacco use in this setting. Methods : Secondary analysis was conducted on cross-sectional data from the Healthy Life Trajectories Initiative (HeLTI) study. Serum cotinine was measured and a cut-off of ≥ 10 ng/mL was classified as tobacco use. Household socio-economic, socio-demographic and health information were collected by an interviewer-administered questionnaire. Results: Cotinine data was available for 1508 participants, of whom 29.2% (n = 441) had cotinine levels indicative of tobacco use. In regression analyses, moderate to severe socio-economic vulnerability (score 2–3 OR 1.66, p = 0.008; score ≥4: OR 1.63, p = 0.026) and multiparity (OR 1.74, p = 0.013) were associated with tobacco use. In addition, alcohol dependence (OR 3.07, p < 0.001) and drug use (OR 4.84, p < 0.001) were associated with tobacco use. Conclusion: Young women with multiple children, moderate to severe socio-economic vulnerability, and alcohol and drug use were identified as more likely to use tobacco, indicating the need for targeted anti-tobacco interventions to curb the impact of tobacco on the growing burden of noncommunicable diseases in this setting. Highlights: Population-specific serum cotinine levels were used to determine tobacco use. Tobacco use was found in 29.2% in young women in an urban African setting. Multiparity and social vulnerability factors were associated with tobacco use. Alcohol and drug use were associated with increased odds of tobacco use. Policies targeted to young women could curb tobacco use and its consequences.